Pengaruh kecerdasan emosional, motivasi belajar dan keaktifan siswaterhadap prestasi belajar matematika siswa sekolah menengah pertama negeri di Kecamatan Ternate Selatan tahun 2013/ 2014 - Rauman Mahmud (Wiyata Dharma: Jurnal Penelitian dan Evaluasi Pendidikan, 2015)
The objective of this research to find out whether the influence of emotional intelligence, learning motivation and actions of students through learning achievement of mathematics, at Junior High School in the sub district of south Ternate 2013/2014.The population of this research is a lot of students in class VIII at Junior High School State 3 and Junior High School State 4 that a total number of 350 students whereas the sample of the students 172 be guided by table Nomogram Herry King. The king of this research is Correlative with the Quantitative approach which the character Ex post facto. The result of this research shows that whether the positive influence is significant of the emotional intelligence, learning motivation and a lot of students to attend together through learning achievement of the mathematics of the students of Junior High School State at south Ternate simultaneously and partial. It is mean that when there are three free variable that is emotional intelligence, learning motivation and a lot of students attend to simultaneous although the partial increase, so string variable of the students learning achievement so high on the contrary, when the three free variable to simultaneous although the partial to descent, so the students learning achievement is very low.